Aerosol and Droplet Particles Contained by Inexpensive Barrier Tent During Mastoidectomy: A COVID-19 Innovation - Andylou Mangubat (Philippine Society of Otolaryngology-Head and Neck Surgery, Inc., 2021)
ABSTRACT